Does Prolonged Monetary Policy Easing Increase Financial Vulnerability? - Cecchetti, Stephen (IMF Working Papers; Working Paper, 2017)
Using firm-level data for approximately 1,000 bank and nonbank financial institutions in 22 countries over the past 15 years we study the impact of prolonged monetary policy easing on risk-taking behavior. We find that the leverage ratio, as well as other measures of firm-level vulnerability, increases for banks and nonbanks as domestic monetary policy easing persists. Cross-border effects are also notable. We find effects of roughly similar magnitude on foreign financial sector firms when the U.S. eases policy. Results appear robust to a variety of specifications, and to be non-linear, with risk-taking behavior rising most quickly at the onset of monetary policy easing.